45. PERCEIVED STIGMA AND COPING STRATEGIES AMONG PARENTS OF CHILDREN WITH AUTISM SPECTRUM DISORDER IN HANOI (Vietnam Journal of Community Medicine, 2025)
Objective: Explore perceived stigma and coping strategies among parents of children with autism spectrum disorder.Methods: This qualitative study was conducted on 11 parents of children with autism spectrum disorder who were undergoing treatment or intervention at the National Children's Hospital and five special education centers in Hanoi through in-depth interviews using a semi-structured interview guide with five open-ended questions.Results: Parents reported feeling most stigmatized when blamed for their child's condition. The coping strategies for stigma used by parents in the study included sharing the diagnosis, educating others about autism spectrum disorder, learning to manage stigma, avoiding certain situations, and equipping their children with necessary skills.Conclusion: These findings emphasize the need for educational programs aimed at reducing stigma perceptions among parents of children with autism.
Keywords: perceived-stigma; parents; autism spectrum disorder; coping strategy.